2013
DOI: 10.1111/dom.12073
|View full text |Cite
|
Sign up to set email alerts
|

Safety, tolerability, pharmacokinetics and pharmacodynamics following 4 weeks' treatment with empagliflozin once daily in patients with type 2 diabetes

Abstract: Oral administration of empagliflozin at doses of 10, 25 or 100 mg once daily over 28 days resulted in significant increases in UGE and reductions in blood glucose compared with placebo, and were well tolerated in patients with type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
200
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(221 citation statements)
references
References 25 publications
18
200
1
2
Order By: Relevance
“…The safety and tolerability of empagliflozin was further confirmed by one of the important study [50]. This research works illustrates that empagliflozin is well tolerated and risk of hypoglycemia is very low.…”
Section: Empagliflozinsupporting
confidence: 59%
See 1 more Smart Citation
“…The safety and tolerability of empagliflozin was further confirmed by one of the important study [50]. This research works illustrates that empagliflozin is well tolerated and risk of hypoglycemia is very low.…”
Section: Empagliflozinsupporting
confidence: 59%
“…Canagliflozin is another C-glucoside and has ~200-fold selectivity for SGLT2 (IC 50 2.2 nM) as compared to SGLT1 (IC 50 0.44µM) [40] ( Table 3). One recent research has shown the potency and selectivity of Canagliflozin towards SGLT2 inhibition.…”
Section: Canagliflozinmentioning
confidence: 99%
“…The most frequently reported adverse effects were pollakiuria (10.3%), nasopharyngitis (9.0%), constipation (9.0%) and headache (7.7%). 17 No adverse drug interactions were found with oral contraceptive pills containing ethinyl estradiol and levonorgestrel. 18 No dose adjustment of empagliflozin is required when coadministered with ramipril, digoxin or verapamil.…”
Section: Empagliflozinmentioning
confidence: 98%
“…11 The effect of empagliflozin on decreasing the fasting plasma glucose is significant and after a period of time, it is said to bring down the glycosylated haemoglobin values as well, though the fall might not be statistically significant. 9 It can be safely given in the patients with hepatic impairment without the need for adjusting the doses.…”
Section: Pharmacodynamicsmentioning
confidence: 99%
“…23 However, in a phase 2 study it was seen that there was no increase in urinary excretion of glucose after the dose was increased from 25 mg to 100 mg, thereby establishing that the clinically relevant dose of empagliflozin is upto 25 mg per day. 9 The most common adverse drug reaction reported with all the SGLT2 inhibitors is the increased risk of genital mycotic infections and to a lesser extent urinary tract infections. This adverse effect is basically an extension of its pharmacological effect.…”
Section: -22mentioning
confidence: 99%